The Role Of Educational System In Secondary Economic Security (Eurasian Journal of Learning and Academic Teaching, 2022)
This article discusses the role of the education system in the economic security of the skilled workforce. The role of man in the economic development of society is also revealed in the study of the problems of strengthening the impact of the education system on the development of the national economy. In addition, conclusions and recommendations are made on the role of the education system in the economic security of the skilled workforce.